Improved genetic algorithms for solving the optimisation tasks for design of access control schemes in computer networks. (2015) - Kotenko, Igor; Saenko, Igor
Access control scheme design is the most important task in the field of computer network security, which has to be solved by security administrators and developers. The access control quality strongly affects such important security properties, as information privacy and accessibility. One of the solutions to this problem is to reduce it to a form of the optimisation task and its subsequent solving by mathematical methods. However, due to the large complexity of this task, applying traditional mathematical methods is very difficult. At the same time, genetic algorithms represent a new and very interesting way to solve this class of problems. This paper suggests an approach for designing access control schemes based on genetic algorithms. To enhance the implementation of genetic operations it proposes a number of significant improvements, which include the multichromosomal representation of individuals in populations, the usage of complex data types to represent genes in chromosomes and the use of special control chromosomes. The experimental evaluation of the approach is discussed. It is demonstrated that the proposed improved genetic algorithms are quite efficient means for access control schemes optimisation in computer networks.